Indicators of informatization of School Education. (Journal of Educational Sciences, 2016)
The article considers the problem of determination of indicators of Informatization of school education. With their help it is possible to describe the current state of the process of Informatization. Monitoring and evaluation of the results of the introduction of information-communication technologies in educational process is crucial whendetermining the strategy of further development of e-learning and e-education in General. The article provides criteria for the selection of indicators developed by the expert group of the European economic Commission (UNECE). Indicators should be relevant to the conditions SMART – S (Specifi c) – specifi c; M (Measurable) is measurable; (Achievable) – Yes; R (Real) is real; T (Times) time-related. To defi ne indicators for measuring the use of ICT in school education we found useful the experience of the UK, where the Toolkit applies a matrixBritish Educational Communications and Technology Agency (VESTA). It includes 32 indicator which helps to determine 6 levels of Informatization of school. Interesting experience of Russia, the Federal indicators ofthe project «Informatization of the education system». The necessity of conducting scientifi c research on the development of indicators for national monitoring system. Keywords:
Keywords: Informatization of education; the national monitoring system of education; inductory; electronic education; level of Informatization of school